PROMOTING STUDENT TEACHERS' TEACHING PRACTICUM WITHIN DESIGNATED SPEAKING CLASS - Sumekto, Didik Rinan (University of Kuningan, 2023)
This study aims at promoting undergraduate student teachers’ teaching practicum that highlights the pedagogical and teaching performance within the designated speaking class. Four senior student teachers participated in five weeks’ teaching practicum through the purposive sampling selection. The method of this study used observation, questionnaire, and teaching practicum documents to facilitate the qualitative analysis in relevance with student teachers’ teaching files, running-methods course, and classroom observations. The core practices of probing pedagogical activities engaged student teachers in intrinsic discussions explicitly and implicitly. The substantial pedagogical matters and their sub-matters were experientially derived from the relevant practicality into the common sense of instruction criteria on planning, implementation, and reflection stages. The discussion substance highlighted daily speaking performance in vocabulary, grammar, pronunciation, fluency, and content among freshmen and sophomores. This study recommends student teachers improve their theoretical and practical teaching methods by accommodating enumeration and sense-making classroom discussion.